ARDS: acute respiratory distress syndrome. (2nd March 2021) - Doyle, Elizabeth
Abstract : Respiratory distress is a common presentation in an emergency and critical care setting. Acute respiratory distress syndrome (ARDS) is an acute onset condition where the lungs cannot provide the patient's vital organs with enough oxygen. ARDS can occur as a result of several underlying triggers. It is important that veterinary nurses know what to look out for in these patients, and how to appropriately nurse them to ensure they are not compromised further.